Web-Based Accounting Information System for Payment Management in Hospitals - Finata, Aghistia Fikka; Anton (TEMA, 2026)
Patient payment management in hospitals requires an integrated system to improve transaction accuracy and efficiency. This study aims to analyze the implementation of a web-based accounting information system (AIS) in patient payment management in a simulated environment. The method used was descriptive qualitative, with data collected through observation, interviews, and documentation. The results showed that the system was able to improve recording accuracy, reduce input errors, and accelerate the administration process and tracking of payment data. However, the system still has limitations due to the lack of comprehensive financial reporting features. The implications of this study indicate that a web-based AIS has the potential to support the effectiveness of patient payment management and serve as the basis for developing a more comprehensive system in hospitals.